Whistleblowing Actions in Fraud Prevention (Case Study of Auditors in Makassar City) - ALAM, Syamsu; WAHYUNI, Nur; ARFAH, Eka Ariaty (PT Keberlanjutan Strategis Indonesia, 2024)
This study examines the act of whistleblowing as a fraud prevention mechanism with a focus on the role of auditors in Makassar City. Whistleblowing, defined as reporting violations of law or ethics to authorities, has great potential in detecting fraud and promoting organizational transparency. This study explores factors that influence auditors' courage to whistleblow, including professional commitment, moral intensity, and cultural and religious aspects. The methodology of this study uses a descriptive qualitative approach with in-depth interviews with a number of auditors in Makassar City. The results of the study indicate that the moral intensity of auditors is a dominant factor in motivating whistleblowing. This study also found that an organizational culture that supports transparency and legal protection for whistleblowers has a significant influence on increasing the effectiveness of the whistleblowing system. This study reveals that whistleblowing can be an effective early detection tool if supported by supportive organizational policies, special training for auditors, and the adoption of anonymous reporting technology. In conclusion, whistleblowing is an important element in fraud prevention efforts. By strengthening professional commitment, increasing moral intensity, and creating a supportive organizational environment, auditors can play a more effective role in identifying and reporting fraud. This study provides practical recommendations for policymakers to develop a safer and more transparent whistleblowing system.